2014
DOI: 10.1111/aogs.12480
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐mediated immune response: a clinical review of the therapeutic potential of human papillomavirus vaccination

Abstract: Prophylactic HPV vaccines have been introduced to reduce the incidence of cervical cancer in young women. Women already infected with HPV could benefit from a therapeutic HPV vaccination. Hence, it is important to continue the development of therapeutic HPV vaccines to lower the rate of HPV-associated malignancies and crucial to evaluate vaccine efficacy clinically. This clinical review represents an attempt to elucidate the theories supporting the development of an HPV vaccine with a therapeutic effect on hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The results reinforce previous studies (4,7,13,14) that show an increase in immune cell activity following vaccination. There is evidence that CMI responses play an important role in the control of HPV infections.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results reinforce previous studies (4,7,13,14) that show an increase in immune cell activity following vaccination. There is evidence that CMI responses play an important role in the control of HPV infections.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies found that a significant cellular mediated immune (CMI) response is induced following HPV vaccination (4,7,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Catch-up vaccination using the standard dosing intervals is also recommended for females and males aged 13 through 26 years old if they were not previously vaccinated or if they have not completed the three-dose series (122). Vaccination in the general population induces a cell-mediated immune response and a strong humoral immune response with antibody titers several times higher than typically seen after natural infections (123,124). Vaccination is recommended regardless of the presence of abnormal cervical cytology, as it may protect against one or more HPV types to which the individual has not been exposed.…”
Section: Prophylactic Vaccinationmentioning
confidence: 99%
“…Clearance of a naturally acquired HPV infection is mediated by a specific cell-mediated immune response in which dendritic cells stimulate T-helper type 1 lymphocytes, which then elicit the production of cytotoxic T lymphocytes that attack infected cells. The ability of an HPV vaccine to stimulate a specific cellular immune response could potentially have a therapeutic effect (124). The current FDA-approved L1 VLP vaccines were designed to prevent HPV infection primarily by stimulating a neutralizing antibody response and were not intended for therapeutic purposes.…”
Section: Therapeutic Vaccinationmentioning
confidence: 99%
“…For these reasons, the possible prevention of cervical cancer draws enormous interest. This has seemed to become a reality after the introduction of the HPV vaccine, which induces a cell–mediated immune response preventing HPV infection for many years [ 2 ].…”
mentioning
confidence: 99%